Cytotoxicity and Phytochemical Screening of Four Species of Plants from Pualas, Lanao del Sur, Philippines - Malawani, Anzhira D.; Nuñeza, Olga M.; Uy, Mylene M.; Senarath, W.T.P.S.K. (Asian Journal of Biological and Life Sciences, 2017)
Utilization of plants as traditional medicine is widely practiced by indigenous communities. This study aimed to test the cytotoxic activities and determine the phytochemicals present in the extracts of the four selected plants: Cyathulageniculata, Peperomiapellucida, Marsdeniatinctoria, and Menthaarvensis that are most commonly used as medicinal plants in Pualas, Lanaodel Sur. For cytotoxicity, the most potent was the ethanol extract of M. tinctoriawith LC50 of 47.86 ppm against the test sample, Artemiasalina. Morever, the phytochemicals present in four plants indicate their potential to be source of drugs. This study illustrates the importance of traditional medicine in the treatment and management of ailments in Pualas, Lanaodel Sur and that confirming the safety and efficacy of the medicinal plants used should be given attention
Keywords: Drugs; Ethanol extract; Medicinal plants; Traditional medicine